Ali Abd Al-Raziq and the Political Movement of the Caliphate System - Yusuf, Maulana (TAJDID, 2020)
This essay attempts to elaborate on the phenomenon of the political movement of the caliphate system according to Ali Abd Al-Raziq. Using critical analysis, this essay concludes that Al-Raziq essentially rejects the caliphate system. According to Al-Raziq, Muslims need to form a state based on reason alone which is influenced by situations and conditions, not based on religion. Therefore, there is no single system in an Islamic state, let alone having a normative justification. Al-Raziq also views that government affairs are worldly matters, not religious matters. He seeks to separate religious affairs from political affairs.